Dynamic High‐Resolution Sonography Compared to Magnetic Resonance Imaging for Diagnosis of Temporomandibular Joint Disk Displacement. (1st January 2015) - Habashi, Hadeel; Eran, Ayelet; Blumenfeld, Israel; Gaitini, Diana
Abstract : Objectives: The purpose of this study was to determine the value of dynamic high‐resolution sonography for evaluation of temporomandibular joint (TMJ) disk displacement compared to magnetic resonance imaging (MRI) with the mouth closed and during the maximal mandibular range of motion. Methods: Dynamic high‐resolution sonography with the mouth closed and during the maximal mandibular range of motion was performed on 39 consecutive patients (78 joints; 13 male and 26 female; age range, 18–77 years; mean age ± SD, 37.23 ± 16.26 years) with TMJ disorders. A TMJ MRI study was performed 1 to 7 days after sonography. We searched for signs of disk displacement and findings compatible with degenerative joint disease. Both studies were performed and interpreted independently by blinded operators. Results: Magnetic resonance imaging depicted 22 normal joints (28.2%), 21 (26.9%) with anterior disk displacement with reduction, 15 (19.2%) with anterior disk displacement without reduction, and 20 (25.6%) with degenerative disease. Sonography depicted 30 normal joints (38.5%), 22 (28.2%) with anterior disk displacement with reduction, 12 (15.4%) with anterior disk displacement without reduction, and 14 (17.9%) with degenerative disease. The overall sensitivity, specificity, and accuracy of sonography for diagnosis of disk displacement were 74.3%, 84.2%, and 77.7%, respectively. The sensitivity, specificity, and accuracy for diagnosis of disk displacement with reduction were 78.6%, 66.7%, and 73.0%, and the values for diagnosis of disk displacement without reduction were 66.7%, 78.6%, and 73.0%. Conclusions: Dynamic high‐resolution sonography is a potential imaging method for diagnosis of TMJ disk displacement and degenerative diseases. Further studies are needed to make dynamic high‐resolution sonography the first‐line test for diagnosis of TMJ disk displacement.